1997
DOI: 10.1080/09640569712038
|View full text |Cite
|
Sign up to set email alerts
|

EIA-Learning from Experience: Changes in the Quality of Environmental Impact Statements for UK Planning Projects

Abstract: This paper draws on a research report recently produced (1996) by the authors for the UK Department of the Environment. The principal aim of the research was to establish clearly what changes, if any, there have been in the quality of Environmental Impact Statements (EISs) since the inception of mandatory EIA in 1988, and to explain reasons for the changes. The paper provides a critique of the meaning of 'quality' in an area such as this. Quality relates both to the EIS and to the EIA process. EIS quality can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
29

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 0 publications
4
35
1
29
Order By: Relevance
“…Since the publication of the Brundtland report in 1987, a growing number of authors state that EIA is one of the tools that can contribute to sustainable development by implementing projects that are environmentally sound, socially acceptable and economically viable. The scope of study in EIA should therefore be broadened to include social and economic aspects (Smith, 1993;Wiesner, 1995;Mostert, 1995;Glasson et al, 1996;Sadler, 1996;Nooteboom, 2007). To achieve these long-term objectives, decision-makers use EIA as a tool for well-informed decision-making.…”
Section: Eia System Performance -A Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the publication of the Brundtland report in 1987, a growing number of authors state that EIA is one of the tools that can contribute to sustainable development by implementing projects that are environmentally sound, socially acceptable and economically viable. The scope of study in EIA should therefore be broadened to include social and economic aspects (Smith, 1993;Wiesner, 1995;Mostert, 1995;Glasson et al, 1996;Sadler, 1996;Nooteboom, 2007). To achieve these long-term objectives, decision-makers use EIA as a tool for well-informed decision-making.…”
Section: Eia System Performance -A Literature Reviewmentioning
confidence: 99%
“…According to the first group, well-informed decision-making makes use of knowledge that is scientifically sound, and open and relevant to debate with the public (Caldwell, 1989;Erickson, 1994;Wood, 1995;Sadler, 1996;Glasson et al, 1996). Some authors from western democratic countries go one step further and state that EIA should have a role in encouraging solutions that are acceptable to politicians, stakeholders and the public in general: EIA as a 'design tool' (Mostert, 1995;Van de Riet, 2003).…”
Section: Eia System Performance -A Literature Reviewmentioning
confidence: 99%
“…At the outset of this research it was hypothesised that EIR quality would improve under the 2006 EIA regulations in South Africa relative to those of 1997, based in part on experience in the UK and Europe that found that the overall quality of EIRs generally improves with time (Badr et al, 2004;Barker and Wood, 1999;European Commission, 1996;Fuller, 1999;Canelas et al, 2005;Glasson et al, 1997;MorrisonSaunders et al, 1999).…”
Section: Conclusion and Way Forwardmentioning
confidence: 99%
“…It is widely acknowledged that EIA legislation and practices rarely conform to idealised (and largely positivist and rationalist) models of the process (Bond and Wathern, 1999;Glasson et al, 1997;Barker and Wood, 1999;Rosenberg et al, 1981). However, this does not E necessarily mean EIA is de facto ineffective.…”
mentioning
confidence: 99%